2018
DOI: 10.1042/cs20180177
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-induced autophagy facilitates hepatic stellate cells activation: a new pathway in liver fibrosis

Abstract: High-mobility group box-1 (HMGB1) plays a context-dependent role in autophagy, which is required for hepatic stellate cells (HSCs) activation. However, the significance of HMGB1-induced HSCs autophagy in liver fibrosis has not been elucidated. Here, we first documented an enrichment of peripheral and intrahepatic HMGB1 signal in hepatitis B virus (HBV)-related liver fibrosis progression, and presented a direct evidence of anatomic proximity of HMGB1 with a-SMA (a marker for HSCs activation) in cirrhotic liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 50 publications
3
40
0
2
Order By: Relevance
“…The working model of HMGB1‐induced HSCs autophagy and fibrogenesis may be summarized as follows: In response to liver injury induced by chronic HBV infection, necrotic hepatocytes passively release HMGB1, which HMGB1 binds to receptor for advanced glycation end product (RAGE) in a paracrine manner, and induces HSCs autophagy and activation, via activation of p‐ERK/JNK MAPK and inhibition of p‐STAT3 and p‐mTOR signaling proteins. Meanwhile, activated HSCs actively secrete HMGB1, which may bind to their RAGE in an autocrine manner, as a positive feedback of exogenous HMGB1 . In this study, we found that both miR‐29b mimic and HMGB1 knockdown blocked the XIST overexpression‐mediated HSCs autophagy and activation.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The working model of HMGB1‐induced HSCs autophagy and fibrogenesis may be summarized as follows: In response to liver injury induced by chronic HBV infection, necrotic hepatocytes passively release HMGB1, which HMGB1 binds to receptor for advanced glycation end product (RAGE) in a paracrine manner, and induces HSCs autophagy and activation, via activation of p‐ERK/JNK MAPK and inhibition of p‐STAT3 and p‐mTOR signaling proteins. Meanwhile, activated HSCs actively secrete HMGB1, which may bind to their RAGE in an autocrine manner, as a positive feedback of exogenous HMGB1 . In this study, we found that both miR‐29b mimic and HMGB1 knockdown blocked the XIST overexpression‐mediated HSCs autophagy and activation.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, HMGB1 is markedly increased in fibrotic liver diseases and plays a pivotal role in liver fibrosis . Recent evidence has indicated that HMGB1 induces autophagy and thus facilitates HSCs activation and liver fibrosis . The working model of HMGB1‐induced HSCs autophagy and fibrogenesis may be summarized as follows: In response to liver injury induced by chronic HBV infection, necrotic hepatocytes passively release HMGB1, which HMGB1 binds to receptor for advanced glycation end product (RAGE) in a paracrine manner, and induces HSCs autophagy and activation, via activation of p‐ERK/JNK MAPK and inhibition of p‐STAT3 and p‐mTOR signaling proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibrosis has received increasingly more attention as a critical pathological feature of NASH because the extent of fibrosis is a major factor for the prognosis of NASH (Chalasani et al, 2018;Diehl & Day, 2017;Drew, 2017). Hepatic fibrosis is pathologically characterized by collagen accumulation in the liver produced by activated stellate cells (Li et al, 2018;Tsuchida & Friedman, 2017). In the present study, the prolonged HF feeding markedly increased the collagen content However, due to the limitation of the lack of histological fibrosis in FIGURE 7 R17 attenuates NAFLD/NASH by activating the AMPK pathway with ATP synthase as an upstream target.…”
Section: Bjpmentioning
confidence: 99%